Individual characteristics as predictors of motivation to use digital library among polytechnic student in Ondo State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Digital libraries offer a lot of advantages for students and this explains why many tertiary institutions including polytechnics in Nigeria have invested in creating various digital libraries. However, many of the libraries often experienced low patronage as students are more inclined to use other source of digital information. In line with this, the study examines the influence of individual characteristics on the motivation to use digital library among polytechnic student in Ondo State, Nigeria. The study adopted the descriptive survey research with the population including 13,407students from two government owned polytechnic in Ondo State. Multistage sampling procedure was followed to select 375 students as sample. A structured questionnaire was used for data collection. The data was analyzed using both inferential and descriptive statistics. The results show that individual characteristics (Adj. R2 = 0. 244, p<0.05) has significant but weak influence on the motivation to use digital library among polytechnic student in Ondo State. The study concluded that the adoption and use of digital libraries underscores the importance of user satisfaction and engagement. It was therefore recommended that polytechnic libraries should provide comprehensive training on how to effectively use digital libraries.